When Narcissus Was a Boy: Origins, Nature, and Consequences of Childhood Narcissism. (27th November 2012) - Thomaes, Sander; Brummelman, Eddie; Reijntjes, Albert; Bushman, Brad J.
Abstract Not all positive self‐views are alike. Developmental researchers increasingly recognize that it is important to distinguish between accurate, well‐balanced positive self‐views and inflated, narcissistic positive self‐views. Narcissism refers to a sense of grandiosity and a strong need to be seen and admired by others. This article reviews current empirical knowledge of narcissistic traits in youths and discusses future challenges and opportunities for this rapidly developing field. Narcissism can be identified from late childhood and has similar manifestations and consequences among youths as it has among adults. Future research will need to uncover the origins and early development of narcissism. The study of childhood narcissism promises to contribute to a more accurate and comprehensive understanding of the development of the self and the consequences of the self.